Assessment of changes in water conservation capacity under land degradation neutrality effects in a typical watershed of Yellow River Basin, China. (April 2023) - Zuo, Depeng; Chen, Guo; Wang, Guoqing; Xu, Zongxue; Han, Yuna; Peng, Dingzhi; Pang, Bo; Abbaspour, Karim C.; Yang, Hong
Graphical abstract: Highlights: Grain for Green Project combat land degradation and improve ecological environment. Afforestation contributes to land degradation neutrality and water conservation. Increase in forest converted from agriculture promotes water conservation capacity. Water conservation capacity was also influenced by rainfall, NDVI, and temperature. Abstract: Large-scale implementation of the Grain for Green Project since 1999, which took the Yellow River Basin (YRB) as the core ecological restoration area, has had an important impact on the hydrological processes and ecological environment. Whether such forest restoration construction is conducive to achieving land degradation neutrality as well as improving water conservation capacity has become a hot research topic. The Yiluo River basin (YLRB), one of the most important water conservation areas in the YRB, was selected as the study area. Firstly, the transfer matrix was used to analyze the changes in the two land use maps in 1990 and 2015 and to determine the transformation relationship between different land use types. Furthermore, land degradation was also investigated for further exploration of the correlation between land degradation neutrality and water conservation. The effects of land use and cover changes (LUCC) on the water conservation capacity across the YLRB were investigated by combining the Soil and Water Assessment Tool (SWAT) model, water conservation assessment method and land use change scenarios method. The results showed that the land degradation area was mainly located in the residential area and agricultural land in the downstream of the YLRB, and the execution of the Grain for Green Project is beneficial in promoting land degradation neutrality and increasing the water conservation capacity. The water conservation capacity across the YLRB approximately increased by 19.30 mm yr −1 as every 10% of agricultural land converted to forest, showing a greater increase in the upstream than that in the downstream. Rainfall, Normalized Difference Vegetation Index (NDVI), and temperature were the primary factors affecting water conservation in the YLRB, while geological lithology also affects the spatial distribution of water conservation. The findings of this study could provide a theoretical basis for water resources and ecological environment protection.